Elucidating population-wide mycobacterial replication dynamics at the single-cell level - Helaine,S; holden,DW; sampson,SL; Mouton,JM (Microbiology, 2016)
Mycobacterium tuberculosis infections result in a spectrum of clinical outcomes, and frequently the infection persists in a latent, clinically asymptomatic state. The within-host bacterial population is likely to be heterogeneous, and it is thought that persistent mycobacteria arise from a small population of viable, but non-replicating (VBNR) cells. These are likely to be antibiotic tolerant and necessitate prolonged treatment. Little is known about these persistent mycobacteria, since they are very difficult to isolate. To address this, we have successfully developed a replication reporter system for use in M. tuberculosis. This approach, termed fluorescence dilution, exploits 2 fluorescent reporters; a constitutive reporter allows the tracking of bacteria, while an inducible reporter enables the measurement of bacterial replication. The application of fluorescent single-cell analysis to characterise intracellular M. tuberculosis identified a distinct subpopulation of non-growing mycobacteria in murine macrophages. The presence of VBNR and actively replicating mycobacteria was observed within the same macrophage after 48 hours of infection. Furthermore, our results suggest that macrophage uptake resulted in enrichment of non- or slowly replicating bacteria (as revealed by DCS treatment); this population is likely to be highly enriched for persisters, based on its drug tolerant phenotype. These results demonstrate the successful application of the novel dual fluorescent reporter system both in vitro and in macrophage infection models to provide a window into mycobacterial population heterogeneity.